Orçamento de obra na construção civil: estudo de caso em uma empresa de pequeno porte da região metropolitana de Porto Alegre/RS - Abati, Leandro Marcos (Universidade do Vale do Rio dos Sinos, 2018)
Lately, Brazil has been facing big political and economic crisis and the construction sector is suffering because of the damages, mainly since 2014. The reduction of the work demand automatically causes the rise on the competition among the companies who are searching for contracts that may guarantee their regular activities. This scenario requires the companies to become more competitive. To do so, it is necessary to improve the internal processes. The construction budgeting is one of the most important because it contributes directly on the company’s management. However, many times there are no suitable budgeting tools for small sized companies. The goal of this study is to evaluate the implantation of construction budgeting process and measure the results achieved with its use. The study took place on a company on the metropolitan region of Porto Alegre, Rio Grande do Sul and it has been structured based on bibliographic references adapted to the reality of the company. As a result, it was created a descriptive budget for one specific construction with mechanisms that provide the control of budgeting tool with addition of the knowledge that may support the culture of use of this process on the future. Lastly, this work contributed to the management of costs, integration of sectors and processes and promoted significant improvements in the purchasing process of the analyzed company.ies.
Keywords: Orçamento; Construção civil; Planejamento; Competitividade; Empresa de pequeno porte; Empresa de pequeno porte; Construction Budgeting; Planning; Competitiveness; Small sized companies